Analisis Virtual Reality Pada Game VR Lounge Room Resident Evil 8 di Game Blink Playstation Padang - Wingsky, Monica; Viola, Zahara Nadinda; Saputra, Firman; Saputra, Topan; Rusdi, Muhammad Ikhsan; Hadi, Aidil Fitra; Wiratama, Agra; Novita, Rini (Universitas Labuhanbatu, 2024)
Virtual Reality (VR) technology has changed the paradigm in the video gaming industry by providing immersive immersive experiences to users. One prominent implementation is in the VR game Lounge Room Resident Evil 8, offered by Blink Playstation Padang. This research aims to analyze the impact of using VR technology on the experience of playing this game at Blink Playstation Padang, especially regarding the level of player satisfaction, level of immersion, and acceleration in improving the playing experience. The research method used is a qualitative approach with a case study design, involving data collection through surveys and interviews with players who have tried VR technology at the facility. The results show that the use of VR increases the immersion and responsiveness of the game, although it also poses challenges such as initial adaptation to the interface and device controls. Overall, players were satisfied with the experience of playing the VR Lounge Room Resident Evil 8 game on Blink Playstation Padang, with a high level of satisfaction with the visual-audio quality and interaction provided by VR technology. This study provides insight into the potential applications of VR technology in the video game industry and its implications for further development.